MARGINAL ANALYSIS AS A TOOL FOR DECISION-MAKING IN A DAIRY COMPANY (Costos y Gestión, 2021)
Small and medium-sized enterprises (SME) generally do not have the appropriate financial management advice. The goal of this project was to evaluate the current management strategies of a small dairy processing company and help its owners make appropriate decisions. To accomplish that, costs marginal analysis was used. Marginal analysis states that the true costs of products or services are the “variable costs”. “Fixed costs”, on the other hand, are those that do not changes with production level. If there is no activity, the fixed costs continue to exist. Variable costing was used to calculate the unit cost of the products (“dulce de leche” – milk caramel – and milk cream), as well as to form an income statement for the production sector, split into the company’s own processing plant and in each of the three third-party processors the company works with. The analysis was expanded incorporating the concept of marginal contribution by scarce factor, which, for this case, is fluid milk. In addition, an income statement was calculated for the commercialization sector, differentiating three distribution areasFor the company’s own processing plant, if a shortage of fluid milk existed, the production of milk caramel in 500 grams cardboard containers should be prioritized (greater amount of marginal contribution -CMG- per liter of milk). Regarding third-party processing plants, “processor 2” had the highest CMG. For distribution areas, zone number 1 should be prioritized. In conclusion, we can affirm that the initial objectives of the research project were accomplished. Costs marginal analysis proved to be a useful tool to guide decision-making for a small dairy processing enterprise.
Keywords: Variabla Costs; Marginal Contribution; Marginal Contribution by Scarce Factor